Conceptualizing Extension Journalism in Multiplatform Media for The Acceleration of Community Food Security Literacy - Metha Madonna; Fikri Reza; Saeful Mujab (Ikatan Sarjana Komunikasi Indonesia, 2026)
The global food crisis is unavoidable when the world’s population is unable to anticipate the phenomena of climate change, increasing environmental pollution, and the shrinking of agricultural land amid an uncontrolled population boom. FAO predicts that food availability will continue to decline, while food demand in developing countries will increase by 60 percent in 2030 and will double by 2050, so that significant action and global community participation are required to face the crisis. Indonesia is categorized as a food-vulnerable country, yet it has the potential to overcome the crisis and even increase food production. Limited support in agricultural resources and food security literacy has resulted in sub?optimal public participation in independent food production. Purpose: (1) to analyze the concept and process of implementing extension journalism in the media; and (2) to formulate strategies for implementing extension journalism in multiplatform media in an effort to enhance community food security literacy. The urgency of this study lies in the notion that the concept of extension journalism can accelerate and enrich public literacy on efforts to build food security at the household and community levels. The method employed is a qualitative approach using the Systematic Literature Review (SLR) method. SLR is used to find and analyze various concepts and models of extension-oriented journalism significantly to reconstruct the current concept of extension journalism. Result: (1) the concept of extension journalism is understood as the dissemination of innovation information through verified conventional mass media (print, terrestrial, and digital); and (2) strategies for implementing extension journalism include regulations and the development of social responsibility awareness among media managers and all journalists involved in content production.